Analisis Dampak Sukuk pada Perekonomian Nasional di Tengah Wabah Covid 19 - Asiyah, Binti Nur; Aini, Indah Nur; Mahardika, Rama Prasetya; Laili, Lyliya Nurul (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam UIN Sunan Ampel Surabaya, 2020)
Sukuk is a form of investment that has an impact on the national economy which is currently weakening due to the Covid-19 pandemic. Covid 19 has had an impact on the faltering of the people's economy from business to financial institutions (sharia and conventional). The state has the need to fulfill the state budget in order to address the problem of the impact of covid 19 quickly. This paper is intended to analyze the impact of sukuk on economic growth during the covid pandemic 19. The process of collecting data is done by analyzing data observed through OJK statistics and collecting various information related to covid-19 and the data are analyzed qualitatively. Based on the results of the study it was found that Sukuk became a source of funds for the government to finance development, thus creating new jobs for the community in the long run. Sukuk provide benefits for the liquidity of Islamic financial institutions due to the impact of covid 19, and also investment facilities for the community. Key Words: Impact; Sukuk; national economiy; Covid-19. Abstrak: Sukuk termasuk bentuk investasi yang memberikan dampak bagi perekonomian nasional yang saat ini melemah karena adanya pandemi Covid-19.Covid 19 telah memberikan dampak bagi tersendatnya perekonomian masyarakat mulai bisnis hingga lembaga keuangan (syariah dan konvensional). Negara memiliki kebutuhan pemenuhan APBN guna menjawab masalah dari dampak covid 19 secara cepat. Paper ini dimaksudkan untuk menganalisis dampak sukuk bagi pertumbuhan ekonomi di masa pandemi covid 19. Proses pengumpulan data dilakukan dengan cara menganalisis data yang diobservasi melalui statistik OJK dan mengumpulkan berbagai informasi terkait covid-19 dan data dianalisis secara kualitatif. Berdasarkan hasil pengkajian diperoleh bahwa Sukuk menjadi sumber dana bagi pemerintah untuk membiayai pembangunan, sehingga menciptakan lapangan kerja baru bagi masyarakat dalam jangka panjangnya. Sukuk memberikan kemanfaatan bagi likuiditas lembaga keuangan syariah akibat dampak covid 19, dan juga sarana investasi bagi masyarakat.. Kata Kunci : Dampak; Sukuk; Perekonomian Nasional; Covid-19.